The Viewpoint of Young Muhammadiyah Intellectuals towards the Religious Minority Groups in Indonesia - Syamsul Arifin; Nafik Muthohirin (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
Muhammadiyah strives to make a positive contribution to the progress of Indonesia. In the first century of the advent, this organization focused on advancing education, health, and compensation to the du‘af?’. Meanwhile, it issued an important point, which emphasized the minority groups through the 47th Congress in Makassar held in 2015. Hence, this article examines several issues concerning the views that underlie young Muhammadiyah intellectuals in voicing partiality towards the religious minority. It also analyzes the role or form of alignments and the implications of these views on thought upheavals within Muhammadiyah internally and nationally. The study discovered that the young intellectuals play a pivotal role in fighting for the basic rights of the religious minority, which continues to face the complicated problem of citizenship. Subsequently, this data has been focused on advocacy and intellectual works, including a literature review of attitude statements, published books, journals, research reports, and opinions in the national mainstream and alternative media.